Integrated DNA methylome and transcriptome analysis reveals the epigenetic regulatory mechanisms underlying maize response to copper stress - Lin Zhao; Mengyan Zhang; Qi Wu; Xi Wu; Zhenyu Yun (PLoS ONE, 2025)
DNA methylation plays a crucial role in plants’ adaptation to environmental stresses. However, the precise role of DNA methylation in regulating the response of maize (Zea mays L.) to copper stress remains incompletely understood. In this study, an integrated analysis of DNA methylome and transcriptome of the hybrid variety “Zhengdan 958” exposed to 1mM Cu stress at seedling stage was conducted using whole genome bisulfite sequencing (WGBS) and RNA-sequencing (RNA-seq). In the comparison between the control and copper stress sample, 3364 differentially expressed genes (DEGs) were detected (1637 upregulated and 1727 downregulated). The WGBS analysis revealed a genome-wide decrease in methylation levels across all cytosine contexts (CG, CHG, and CHH) under copper stress, with 1545 gene body hypomethylated differentially methylated genes (DMGs) and 1806 promoter hypomethylated DMGs. By integrating the analysis of DEGs and hypomethylated DMGs, we identified two predominant patterns of epigenetic regulation: (1) gene body CHG/CHH hypomethylation associated with transcriptional activation of metabolic and stress-response genes, and (2) promoter CHH hypomethylation linked to repression of developmental regulators and signaling components. This study provides valuable data for the epigenetic regulation of copper stress responses and identifies potential targets for developing stress-tolerant maize varieties through epigenetic breeding approaches.